Application of adaptive client concept for the technical diagnoctics computer system - Горбійчук, Михайло Іванович; Слабінога, Мар’ян Остапович (Eastern-European Journal of Enterprise Technologies, 2014)
The concept of an adaptive client in the client-server architecture of an automated computer system for identifying the technical condition of industrial facilities was discussed in the paper. The existing solutions of the client-server architectures were considered, their advantages and disadvantages were given. The selection of hardware and software of a test system, meeting the set forth specifications, was justified. The task was to design an algorithm and software implementation of the concept of an adaptive client. The theoretical basis of the client was substantiated, the behavior was described and the operation algorithm flowchart for software implementation was given. The results of the adaptive client with respect to the same operation of “thin” and “thick” clients when making analytical calculations of the different levels of complexity. The conclusion about the feasibility of implementing this concept into the automated computer system of technical diagnostics was made. The advantages of this approach compared with other implementations of the client-server architecture were given.